Conductive polymer dispersion, conductive polymer film and electrolytic capacitor
Patent Information
- Application Number
- JP2021023887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-02-18
AI Technical Summary
【0013】 本発明によれば、塗布性に優れた導電性高分子分散液、前記導電性高分子分散液により形成される導電性高分子膜、および前記導電性高分子膜を有する電解コンデンサを提供することができる。
Smart Images

Figure 0007638722000001 
Figure 0007638722000002 
Figure 0007638722000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer dispersion having excellent coatability, a conductive polymer film formed from the conductive polymer dispersion, and an electrolytic capacitor having the conductive polymer film. [Background technology]
[0002] Due to their high electrical conductivity, conductive polymers are used, for example, as transparent electrode materials, hole transport materials, antistatic materials, electrolytes (solid electrolytes) for electrolytic capacitors, and the like.
[0003] As the conductive polymer for this application, for example, one obtained by chemical oxidative polymerization or electrolytic oxidative polymerization of thiophene or its derivatives is used.
[0004] Also, as a method of using such conductive polymers as, for example, electrolytes in electrolytic capacitors, a method is known in which a substrate such as a capacitor element is immersed in a dispersion liquid in which a conductive polymer is dispersed in a solvent, and then removed and dried to remove the solvent, thereby forming a solid electrolyte layer (conductive polymer film) on the surface of the substrate (Patent Document 1, etc.). Furthermore, dispersion liquids in which conductive polymers are dispersed in a solvent are used not only for forming solid electrolyte layers in electrolytic capacitors, but also for forming conductive patterns and conductive films (Patent Document 2, etc.).
[0005] As a solvent for the dispersion of the conductive polymer as described above, water is often used, which is also used as a synthetic solvent for the conductive polymer. In addition, in order to improve the conductivity of the solid electrolyte layer containing the conductive polymer, a high-boiling point solvent such as ethylene glycol, propylene glycol, or dimethyl sulfoxide may be used together with water (Patent Documents 1 and 2 mentioned above).
[0006] Furthermore, it has been proposed to use a diol compound as a solvent for a conductive polymer dispersion (Patent Documents 3 to 5). For example, Patent Document 3 discloses that a conductive polymer dispersion obtained by concentrating a raw material aqueous dispersion containing a conductive polymer and water until the solid content concentration of the conductive polymer reaches a specific value and mixing this with a diol compound has excellent printability for screen printing. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2011-60980 A (paragraphs
[0034] ,
[0035] ,
[0043] ,
[0044] , etc.) [Patent Document 2] JP 2014-152320 A (paragraphs
[0042] to
[0044] , etc.) [Patent Document 3] JP 2019-104858 A [Patent Document 4] JP 2019-116537 A [Patent Document 5] JP 2020-7470 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, further improvement is required regarding the coatability of the conductive polymer dispersion, for example, from the viewpoint of forming a conductive polymer film with better characteristics.
[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a conductive polymer dispersion having excellent coatability, a conductive polymer film formed from the conductive polymer dispersion, and an electrolytic capacitor having the conductive polymer film. [Means for solving the problem]
[0010] The conductive polymer dispersion of the present invention, which has achieved the above-mentioned object, comprises a π-conjugated conductive polymer doped with a polyanion and a solvent, and is characterized in that the solvent contains water, a compound containing two or more hydroxyl groups, and an aprotic polar solvent having a boiling point of 100°C or higher.
[0011] The conductive polymer film of the present invention is characterized in that it is formed by applying the conductive polymer dispersion of the present invention to a substrate and drying the resulting coating film.
[0012] Furthermore, the electrolytic capacitor of the present invention is characterized in that it uses the conductive polymer film of the present invention as an electrolyte. Effect of the Invention
[0013] According to the present invention, it is possible to provide a conductive polymer dispersion having excellent coatability, a conductive polymer film formed from the conductive polymer dispersion, and an electrolytic capacitor having the conductive polymer film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The conductive polymer dispersion of the present invention contains a π-conjugated conductive polymer doped with a polyanion and a solvent, and the solvent contains water, a compound containing two or more hydroxyl groups, and an aprotic polar solvent having a boiling point of 100° C. or higher.
[0015] The conductive polymer dispersion of the present invention has excellent coatability due to the action of the compound containing two or more hydroxyl groups, which is the solvent, and the aprotic polar solvent having a boiling point of 100°C or higher. Even when the conductive polymer dispersion is repeatedly coated onto a large number of substrates, etc., it is unlikely to cause smearing or bleeding, and can form a coating film with good properties.
[0016] The conductive polymer film of the present invention formed by using the conductive polymer dispersion of the present invention has a low resistance value and good characteristics. Furthermore, the electrolytic capacitor of the present invention using the conductive polymer film of the present invention as an electrolyte also has good characteristics.
[0017] Examples of the π-conjugated conductive polymer (hereinafter, sometimes simply referred to as "conductive polymer") related to the conductive polymer dispersion of the present invention include those obtained by polymerizing monomers such as thiophene or its derivatives, pyrrole or its derivatives, and aniline or its derivatives. When obtaining a conductive polymer film using the conductive polymer dispersion of the present invention, for example, it is preferable to use a conductive polymer obtained by polymerizing thiophene or its derivatives. This is because the conductive polymer obtained by polymerizing thiophene or its derivatives has superior conductivity and heat resistance compared to conductive polymers obtained by polymerizing other monomers.
[0018] Examples of the thiophene derivative in thiophene or its derivative include 3,4-ethylenedioxythiophene, 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, and alkylated ethylenedioxythiophene in which the above-mentioned 3,4-ethylenedioxythiophene is modified with an alkyl group. The number of carbon atoms in the alkyl group or alkoxy group is preferably 1 or more and is preferably 16 or less, more preferably 10 or less, and even more preferably 4 or less.
[0019] To explain in detail about alkylated ethylenedioxythiophene obtained by modifying the above-mentioned 3,4-ethylenedioxythiophene with an alkyl group, the above-mentioned 3,4-ethylenedioxythiophene and alkylated ethylenedioxythiophene correspond to compounds represented by the following general formula (1).
[0020] [ka]
[0021] In general formula (1), R 1 is hydrogen or an alkyl group having 1 to 10 carbon atoms.
[0022] And, R in the above general formula (1) 1 The compound where R is hydrogen is 3,4-ethylenedioxythiophene, and its IUPAC name is "2,3-Dihydro-thieno[3,4-b][1,4]dioxine." However, this compound is more often represented by its general name "3,4-ethylenedioxythiophene" than by its IUPAC name, so in this specification, this "2,3-dihydro-thieno[3,4-b][1,4]dioxine" is represented as "3,4-ethylenedioxythiophene." And, R in the above general formula (1) 1 When R is an alkyl group, the alkyl group preferably has 1 to 10 carbon atoms, and more preferably has 1 to 4 carbon atoms. That is, the alkyl group is particularly preferably a methyl group, an ethyl group, a propyl group, or a butyl group. Specific examples of these include R in the general formula (1). 1 The compound where R is a methyl group is called "2-Methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" in IUPAC name, but in the following of this specification, this will be abbreviated to "methylated ethylenedioxythiophene". 1 The IUPAC name for the compound with an ethyl group is "2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine," but in this specification, this is abbreviated to "ethylated ethylenedioxythiophene."
[0023] R in general formula (1) 1The compound in which R is a propyl group is called "2-propyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" in IUPAC name, but in this specification, this is abbreviated to "propylated ethylenedioxythiophene". 1 The IUPAC name for a compound in which the butyl group is used is "2-butyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine", but in this specification, this is abbreviated to "butylated ethylenedioxythiophene". Also, in this specification, "2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" is abbreviated to "alkylated ethylenedioxythiophene". Among these alkylated ethylenedioxythiophenes, methylated ethylenedioxythiophene, ethylated ethylenedioxythiophene, propylated ethylenedioxythiophene, and butylated ethylenedioxythiophene are preferred.
[0024] In addition, 3,4-ethylenedioxythiophene (i.e., 2,3-dihydro-thieno[3,4-b][1,4]dioxine) and alkylated ethylenedioxythiophene (i.e., 2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine) can be mixed and used, and in that case, the mixing ratio, in molar ratio, is preferably 0.05:1 to 1:0.1, more preferably 0.1:1 to 1:0.1, even more preferably 0.2:1 to 1:0.2, and particularly preferably 0.3:1 to 1:0.3.
[0025] As the polyanion, for example, the following (A), (B) or (C) can be mentioned as preferred, and one or more of these can be used.
[0026] (A) Polystyrene sulfonic acid.
[0027] (B) A copolymer of styrenesulfonic acid and at least one non-sulfonic acid monomer selected from the group consisting of acrylic acid esters, methacrylic acid esters, and unsaturated hydrocarbon-containing alkoxysilane compounds or hydrolysates thereof.
[0028] (C) Water-soluble polyester resin.
[0029] The polystyrene sulfonic acid (A) preferably has a weight average molecular weight of 10,000 to 1,000,000.
[0030] Examples of acrylic acid esters that are monomers for the copolymer (B) include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, stearyl acrylate, cyclohexyl acrylate, diphenylbutyl acrylate, dimethylaminoethyl acrylate, diethylaminoethyl acrylate, sodium sulfohexyl acrylate, glycidyl acrylate, methylglycidyl acrylate, and hydroxyalkyl acrylate (hydroxymethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, etc.). Among these, hydroxyalkyl acrylates having an alkyl group of 1 to 4 carbon atoms, such as hydroxymethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxybutyl acrylate, are preferred in terms of their properties as a dopant when copolymerized with styrenesulfonic acid. In addition, those containing a glycidyl group, such as glycidyl acrylate and methylglycidyl acrylate, become structures containing hydroxyl groups by ring-opening of the glycidyl group, and therefore those having a glycidyl group are also preferred in terms of their properties as a dopant when copolymerized with styrenesulfonic acid, similarly to hydroxyalkyl acrylates.
[0031] Examples of methacrylate esters that serve as monomers for the copolymer of component (B) include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, stearyl methacrylate, cyclohexyl methacrylate, diphenylbutyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, sodium sulfohexyl methacrylate, glycidyl methacrylate, methylglycidyl methacrylate, hydroxyalkyl methacrylates (hydroxymethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, hydroxyhexyl methacrylate, hydroxystearyl methacrylate, etc.), hydroxypolyoxyethylene methacrylate, methoxyhydroxypropyl methacrylate, ethoxyhydroxypropyl methacrylate, dihydroxypropyl methacrylate, dihydroxybutyl methacrylate, and the like. Among these, hydroxyalkyl methacrylates having an alkyl group carbon number of 1 to 4, such as hydroxymethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate, are preferred in terms of their properties as a dopant when copolymerized with styrenesulfonic acid. In addition, those containing a glycidyl group, such as glycidyl methacrylate and methylglycidyl methacrylate, become structures containing a hydroxyl group by ring-opening of the glycidyl group, and therefore those having a glycidyl group are also preferred in terms of their properties as a dopant when copolymerized with styrenesulfonic acid, similarly to hydroxyalkyl methacrylate.
[0032] Examples of unsaturated hydrocarbon-containing alkoxysilane compounds or hydrolysates thereof that serve as monomers for the copolymer of component (B) include unsaturated hydrocarbon-containing alkoxysilane compounds and hydrolysates thereof, such as 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyldimethylmethoxysilane, 3-methacryloxypropyldimethylethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxymethyldimethoxysilane, 3-acryloxymethyldiethoxysilane, 3-acryloxytriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, p-styrylmethyldimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, and vinyldimethylmethoxysilane. For example, when the unsaturated hydrocarbon-containing alkoxysilane compound is the above-mentioned 3-methacryloxypropyltrimethoxysilane, the hydrolysis product of the unsaturated hydrocarbon-containing alkoxysilane compound is 3-methacryloxytrihydroxysilane, which is a structure in which methoxy groups are hydrolyzed to hydroxyl groups, or silanes are condensed to form oligomers, and the methoxy groups not used in the reaction are hydroxyl groups.As the unsaturated hydrocarbon-containing alkoxysilane compound, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, p-styryltrimethoxysilane, vinyltrimethoxysilane, etc. are preferred from the viewpoint of the properties as a dopant when copolymerized with styrenesulfonic acid.
[0033] In the copolymer (B), the ratio of styrene sulfonic acid to at least one non-sulfonic acid monomer selected from the group consisting of methacrylic acid esters, acrylic acid esters, and unsaturated hydrocarbon-containing alkoxysilane compounds or hydrolysates thereof is preferably 1:0.01 to 0.1:1 by mass.
[0034] The copolymer of the above-mentioned styrene sulfonic acid and at least one non-sulfonic acid monomer selected from the group consisting of methacrylic acid esters, acrylic acid esters, and unsaturated hydrocarbon-containing alkoxysilane compounds or hydrolysates thereof preferably has a weight average molecular weight of about 5,000 to 500,000 in terms of water solubility and properties as a dopant, and more preferably has a weight average molecular weight of about 40,000 to 200,000.
[0035] Examples of the water-soluble polyester (C) include sulfonated polyester.
[0036] The conductive polymer dispersion contains, as a solvent, water, a compound containing two or more hydroxyl groups, and an aprotic polar solvent having a boiling point of 100° C. or higher.
[0037] Examples of compounds containing two or more hydroxyl groups include polyhydric alcohols such as ethylene glycol (EG), propylene glycol (PG), butanediol, and glycerin, and the conductive polymer dispersion liquid may contain only one of these, or may contain two or more of them.
[0038] The aprotic polar solvent contained as a solvent in the conductive polymer dispersion has a boiling point of 100°C or higher. This makes it possible to suppress the evaporation of the solvent when the conductive polymer dispersion is applied to form a coating film, thereby enabling the fluidity of the dispersion to be maintained for a long period of time, and therefore makes it possible to ensure good coatability even when the dispersion is repeatedly used to form a coating film.
[0039] Examples of aprotic polar solvents having a boiling point of 100°C or higher include dimethylsulfoxide (DMSO, boiling point: 189°C), N-methylformamide (MF, boiling point: 180 to 185°C), N,N-dimethylformamide (DMF, boiling point: 153°C), N-methylacetamide (MAc, boiling point: 205°C), and N,N-dimethylacetamide (DMAc, boiling point: 165°C). The conductive polymer dispersion may contain only one of these, or may contain two or more of them.
[0040] In the conductive polymer dispersion, the content of each solvent in the total amount of the conductive polymer dispersion is desirably as follows, from the viewpoint of ensuring better coatability for a long period of time.
[0041] The content of the compound containing two or more hydroxyl groups in the total amount of the conductive polymer dispersion is preferably 80 mass % or less, more preferably 70 mass % or less, and is preferably 40 mass % or more.
[0042] The content of the aprotic polar solvent having a boiling point of 100° C. or higher in the total amount of the conductive polymer dispersion is preferably 0.1 mass % or more, more preferably 5 mass % or more, and is preferably 30 mass % or less, and more preferably 20 mass % or less.
[0043] The water content in the total amount of the conductive polymer dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less.
[0044] In the conductive polymer dispersion, the components other than the solvent may be only the π-conjugated conductive polymer doped with a polyanion, and may further contain resin components such as polyvinyl alcohol resin, epoxy resin, polyester resin, acrylic resin, melamine resin, urethane resin, etc. The content of the π-conjugated conductive polymer doped with a polyanion in the total amount of the conductive polymer dispersion is preferably, for example, 1 to 10 mass %.
[0045] The conductive polymer dispersion can be obtained, for example, by synthesizing a conductive polymer by oxidative polymerization in an aqueous liquid (water or a mixture of water and a water-miscible solvent) containing a polyanion as a dopant, producing an aqueous dispersion in which the conductive polymer doped with the polyanion is dispersed in an aqueous liquid containing water, and then adding a compound containing two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100°C or higher to this aqueous dispersion.
[0046] Examples of the water-miscible solvent constituting the aqueous liquid used in synthesizing the conductive polymer include methanol, ethanol, propanol, acetone, and acetonitrile. The mixing ratio of these water-miscible solvents to water is preferably 50 mass % or less of the entire aqueous liquid.
[0047] The oxidative polymerization for synthesizing the conductive polymer can be either chemical oxidative polymerization or electrolytic oxidative polymerization.
[0048] As an oxidizing agent for carrying out chemical oxidative polymerization, for example, a persulfate is used. As the persulfate, for example, ammonium persulfate, sodium persulfate, potassium persulfate, calcium persulfate, barium persulfate, etc. are used.
[0049] In the chemical oxidative polymerization, the polymerization conditions are not particularly limited, but the temperature during the chemical oxidative polymerization is preferably 5°C to 95°C, more preferably 10°C to 30°C, and the polymerization time is preferably 1 hour to 72 hours, more preferably 8 hours to 24 hours.
[0050] The electrolytic oxidation polymerization can be carried out at a constant current or a constant voltage. For example, when the electrolytic oxidation polymerization is carried out at a constant current, the current value is 0.05 mA / cm 2 ~10mA / cm 2 is preferred, and 0.2 mA / cm 2 ~4mA / cm 2When electrolytic oxidation polymerization is performed at a constant voltage, the voltage is preferably 0.5 V to 10 V, and more preferably 1.5 V to 5 V. The temperature during electrolytic oxidation polymerization is preferably 5° C. to 95° C., and particularly preferably 10° C. to 30° C. The polymerization time is preferably 1 hour to 72 hours, and more preferably 8 hours to 24 hours. In addition, ferrous sulfate or ferric sulfate may be added as a catalyst in the electrolytic oxidation polymerization.
[0051] The conductive polymer obtained as described above (conductive polymer doped with polyanion) is obtained in a dispersed state in water or an aqueous liquid immediately after polymerization, and contains persulfate as an oxidizing agent, iron sulfate used as a catalyst, and its decomposition products. Therefore, it is preferable to disperse the impurities in the aqueous dispersion of the conductive polymer containing the impurities through a dispersing machine such as an ultrasonic homogenizer, a high-pressure homogenizer, or a planetary ball mill, and then remove the metal components with a cation exchange resin. The particle size of the conductive polymer measured by the dynamic light scattering method at this time is preferably 100 μm or less, more preferably 10 μm or less, and preferably 0.01 μm or more, and more preferably 0.1 μm or more. Thereafter, it is preferable to remove the products generated by the decomposition of the oxidizing agent or catalyst by ethanol precipitation, ultrafiltration, anion exchange resin, etc.
[0052] A compound containing two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100° C. or higher are added to the aqueous dispersion of the conductive polymer thus obtained to obtain the conductive polymer dispersion of the present invention. Furthermore, if necessary, after the compound containing two or more hydroxyl groups and the aprotic polar solvent having a boiling point of 100° C. or higher are added, the water content in the conductive polymer dispersion may be adjusted by concentration.
[0053] The conductive polymer dispersion of the present invention obtained as described above is applied to a substrate by, for example, coating using various coaters such as a roll coater, bar coater, blade coater, or spin coater, printing by flexographic printing, gravure printing, screen printing, offset printing, or the like, dipping, spraying, or the like to form a coating film, which is then dried to obtain the conductive polymer film of the present invention. The conductive polymer dispersion of the present invention is particularly excellent in coatability during printing and suitability for repeated printing, and is capable of forming a coating film with good properties, so that the conductive polymer film of the present invention obtained by drying it has good properties, for example, excellent conductivity.
[0054] As can be seen from a comparison of the characteristics (surface resistance value) of the conductive polymer membranes of Examples 2-1 to 2-19 and Comparative Examples 2-2 to 2-5 described later, the conductive polymer membrane of the present invention has clearly different characteristics from a conductive polymer membrane formed from, for example, a conductive polymer dispersion liquid that does not contain an aprotic polar solvent having a boiling point of 100° C. or higher, and it is presumed that there is some structural difference between the two. However, since it is difficult to specify the structural difference between the two conductive polymer membranes at present, the conductive polymer membrane of the present invention is specified by the manufacturing process as described above.
[0055] The conductive polymer film of the present invention can be used as an electrolyte for an electrolytic capacitor. That is, the electrolytic capacitor of the present invention has the conductive polymer film of the present invention as an electrolyte. Since the conductive polymer film of the present invention has good properties and excellent conductivity as described above, the electrolytic capacitor of the present invention using this as an electrolyte has excellent characteristics.
[0056] Electrolytic capacitors include aluminum electrolytic capacitors, tantalum electrolytic capacitors, niobium electrolytic capacitors, etc., and among the aluminum electrolytic capacitors, there are wound type aluminum electrolytic capacitors and laminated or flat type aluminum electrolytic capacitors.
[0057] For example, as a capacitor element for a wound aluminum electrolytic capacitor, it is preferable to use a capacitor prepared by etching the surface of an aluminum foil, then chemically treating it to form a dielectric layer on an anode, attaching a lead terminal to the anode, attaching a lead terminal to a cathode made of aluminum foil, and winding the anode with the lead terminals and the cathode with a separator interposed therebetween.
[0058] The above-mentioned capacitor element is used to manufacture a wound aluminum electrolytic capacitor, for example, as follows.
[0059] The conductive polymer dispersion of the present invention is applied to the surface of the capacitor element and dried to form a solid electrolyte layer made of the conductive polymer film of the present invention, and the capacitor element having the solid electrolyte layer is exterior-packaged with an exterior material to produce a wound aluminum electrolytic capacitor.
[0060] In producing electrolytic capacitors other than wound aluminum electrolytic capacitors, for example, stacked or flat aluminum electrolytic capacitors, tantalum electrolytic capacitors, niobium electrolytic capacitors, etc., a capacitor element having an anode made of a porous body of a valve metal such as aluminum, tantalum, niobium, etc. and a dielectric layer made of an oxide film of the valve metal is used, and the conductive polymer dispersion of the present invention is applied to the surface of the capacitor element and dried to form a solid electrolyte layer made of the conductive polymer film of the present invention, and then a carbon paste and a silver paste are applied, dried, and then packaged, thereby producing a stacked or flat aluminum electrolytic capacitor, tantalum electrolytic capacitor, niobium electrolytic capacitor, etc.
[0061] In addition, prior to printing the conductive polymer dispersion, a base layer that will become a part of the solid electrolyte layer may be formed by directly synthesizing a conductive polymer on the surface of the capacitor element by so-called "in-situ polymerization", and then the conductive polymer dispersion may be applied to the surface of this base layer and dried to form a solid electrolyte layer containing the above-mentioned base layer and a part derived from the conductive polymer dispersion. For example, when the pores of the capacitor element are so fine that it is difficult to sufficiently penetrate the conductive polymer (particles) in the conductive polymer dispersion, it is possible to obtain an electrolytic capacitor with better characteristics by filling the pores to a certain extent with the conductive polymer by "in-situ polymerization" and then forming a solid electrolyte layer using the conductive polymer dispersion. The "in-situ polymerization" on the surface of the capacitor element can be carried out, for example, at 10 to 300 ° C. and for 1 to 180 minutes using the same materials (monomers, dopants, solvents, oxidizers, etc.) as those used in the synthesis of the conductive polymer to prepare the conductive polymer dispersion.
[0062] The electrolytic capacitor of the present invention can be used for the same purposes as conventionally known electrolytic capacitors. The conductive polymer film of the present invention can be used as an electrolyte for the electrolytic capacitor of the present invention, and the conductive polymer dispersion of the present invention can form the conductive polymer film of the present invention. EXAMPLES
[0063] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0064] <Production example of polyanion> (Production Example 1: Production of polystyrene sulfonic acid) 1 L of pure water was placed in a 2 L separable flask equipped with a stirrer, and 222.7 g of sodium styrenesulfonate (199 g as styrenesulfonic acid) was added and dissolved therein. Then, 1 g of ammonium persulfate was added as an oxidizing agent to the obtained solution, and a polymerization reaction was carried out for 12 hours.
[0065] Thereafter, 100 g of a cation exchange resin (Amberlite 120B (product name), manufactured by Organo Corporation) was added to the reaction liquid after the polymerization reaction, and the mixture was stirred for 1 hour with a stirrer. The mixture was then filtered through filter paper No. 131 manufactured by Toyo Roshi Kaisha, Ltd. This treatment with the cation exchange resin and filtration were repeated three times to remove all of the cationic components in the liquid, thereby obtaining polystyrene sulfonic acid dissolved in water.
[0066] The obtained polystyrene sulfonic acid was analyzed using a high performance liquid chromatography (HPLC) system with a gel permeation chromatography (GPC) column, and the weight average molecular weight of the polystyrene sulfonic acid, estimated using dextran as a standard, was 90,000.
[0067] (Production Example 2: Production of a copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane) In this polyanion production example, the production of a copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane, an unsaturated hydrocarbon-containing alkoxysilane compound, with a mass ratio of 9:1 will be described. Note that in the following production examples, the composition of the copolymer will be indicated in terms of the mass ratio of the monomers at the start of use.
[0068] 1 L of pure water was placed in a 2 L separable flask equipped with a stirrer, and 212.7 g of sodium styrenesulfonate (190 g as styrenesulfonic acid) and 10 g of 3-methacryloxypropyltrimethoxysilane were added and dissolved therein. Then, 1 g of ammonium persulfate was added as an oxidizing agent to the resulting solution, and a polymerization reaction between styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane was carried out for 12 hours.
[0069] Thereafter, 100 g of a cation exchange resin (Amberlite 120B (product name), manufactured by Organo Corporation) was added to the reaction liquid after the polymerization reaction, and the mixture was stirred with a stirrer for 1 hour. The mixture was then filtered through No. 131 filter paper manufactured by Toyo Roshi Kaisha, Ltd. This treatment with the cation exchange resin and filtration were repeated three times to remove all of the cationic components in the liquid, thereby obtaining a copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane in a dissolved state in water.
[0070] The obtained copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane was analyzed using an HPLC system with a GPC column, and the weight average molecular weight of the copolymer, estimated using dextran as a standard, was 80,000.
[0071] <Production Example of Conductive Polymer Water Dispersion> (Production Example 1) In Production Example 1 of the conductive polymer aqueous dispersion, the conductive polymer aqueous dispersion was produced using the polystyrene sulfonic acid obtained in Production Example 1 of the polyanion as a dopant.
[0072] 600 g of the 4% by mass aqueous solution of polystyrene sulfonic acid obtained in Production Example 1 of the above polyanion was placed in a stainless steel vessel with an internal volume of 1 L, and 0.3 g of ferrous sulfate heptahydrate was added as a catalyst and dissolved therein. 4 mL of 3,4-ethylenedioxythiophene was slowly added dropwise thereto. The reaction solution in the vessel was stirred with a stainless steel stirring spring, an anode was attached to the vessel, a cathode was attached to the stirring spring, and a current of 1 mA / cm was applied. 2 The electrochemical oxidation was carried out at a constant current of 0.05V for 18 hours to synthesize a conductive polymer doped with polyanions.
[0073] The reaction solution after electrolytic oxidation polymerization was diluted 4 times with water, and then dispersed for 30 minutes using an ultrasonic homogenizer (US-T300 (trade name), manufactured by Nippon Seiki Co., Ltd.). Then, 100 g of a cation exchange resin (Amberlite 120B (trade name), manufactured by Organo Co., Ltd.) was added to the reaction solution, which was stirred for 1 hour using a stirrer. It was then filtered using filter paper No. 131 manufactured by Toyo Roshi Co., Ltd. This treatment with the cation exchange resin and filtration were repeated three times to remove all cationic components in the solution.
[0074] The liquid after the above treatment was passed through a filter with a pore size of 1 μm, and the liquid that passed through was treated with an ultrafiltration device (Vivaflow200 (trade name), manufactured by Sartorius, molecular weight cutoff 50,000) to remove free low molecular weight components in the liquid. The liquid after this treatment was diluted with water to adjust the concentration of the conductive polymer doped with polyanion, thereby obtaining an aqueous dispersion (1) of the conductive polymer with a concentration of 2.0 mass%.
[0075] (Production Example 2) In this Production Example 2, a water dispersion of a conductive polymer was produced using the copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane in a mass ratio of 9:1 obtained in Production Example 2 of the polyanion as a dopant.
[0076] That is, the aqueous solution of the polyanion used was changed to 600 g of a 4 mass% aqueous solution of the copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane obtained in Polyanion Production Example 2, and the same procedure was followed as in Production Example 1 to obtain an aqueous dispersion (2) of the conductive polymer doped with the polyanion copolymer of styrenesulfonic acid and 3-methacryloxypropyltrimethoxysilane at a concentration of 2.0 mass%.
[0077] (Production Example 3) 600 g of an aqueous solution of sulfonated polyester (manufactured by GOO Chemical Industry Co., Ltd., PLASCOAT Z-561 (trade name), number average molecular weight 27,000) was placed in a stainless steel vessel with an internal volume of 1 L, 0.5 g of ferrous sulfate heptahydrate was added, and 4 mL of 3,4-ethylenedioxythiophene was slowly added dropwise thereto. The reaction solution in the vessel was stirred with a stainless steel stirring blade, an anode was attached to the vessel, a cathode was attached to the base of the stirring blade, and a current of 1 mA / cm was applied. 2 A conductive polymer doped with the sulfonated polyester, which is a polyanion, was synthesized by electrolytic oxidation polymerization at a constant current of 1000 V for 18 hours. The ratio of the sulfonated polyester, which is the dopant in the electrolytic oxidation polymerization, to the polymerizable monomer 3,4-ethylenedioxythiophene was sulfonated polyester:3,4-ethylenedioxythiophene=1:0.2 by mass.
[0078] The reaction solution after electrolytic oxidation polymerization was diluted 6 times with water, and then dispersed for 30 minutes using an ultrasonic homogenizer (US-T300 (trade name), manufactured by Nippon Seiki Co., Ltd.). Then, 100 g of a cation exchange resin (Amberlite 120B (trade name), manufactured by Organo Co., Ltd.) was added to the reaction solution and stirred for 1 hour using a stirrer. The solution was then filtered using filter paper No. 131 manufactured by Toyo Roshi Co., Ltd. This treatment with the cation exchange resin and filtration were repeated three times to remove all cationic components such as iron ions from the solution.
[0079] The liquid after the above treatment was passed through a filter with a pore size of 1 μm, and the liquid that passed through was treated with an ultrafiltration device (Vivaflow200 (trade name), manufactured by Sartorius, molecular weight cutoff 50,000) to remove free low molecular weight components in the liquid. The liquid after this treatment was diluted with water to adjust the concentration of the conductive polymer doped with polyanion, thereby obtaining an aqueous dispersion (3) of the conductive polymer with a concentration of 5.0 mass%.
[0080] <Conductive polymer dispersion> (Example 1-1) To 300 g of the aqueous dispersion of the conductive polymer (1), 60 g of propylene glycol and 20 g of dimethyl sulfoxide were added as solvents and stirred with a stirrer for 1 hour. The water was then removed under reduced pressure with an evaporator to obtain a conductive polymer dispersion having a polyanion-doped conductive polymer concentration of 6 mass%.
[0081] (Example 1-2) A conductive polymer dispersion having a polyanion-doped conductive polymer concentration of 6 mass% was obtained in the same manner as in Example 1-1, except that the conductive polymer aqueous dispersion was changed to conductive polymer aqueous dispersion (2).
[0082] (Examples 1-3) A conductive polymer dispersion having a polyanion-doped conductive polymer concentration of 12 mass% was obtained in the same manner as in Example 1-1, except that the conductive polymer aqueous dispersion was changed to a conductive polymer aqueous dispersion (3): 240 g.
[0083] (Examples 1 to 4) A conductive polymer dispersion having a polyanion-doped conductive polymer concentration of 12 mass% was obtained in the same manner as in Example 1-1, except that the conductive polymer aqueous dispersion was changed to a mixture of 60 g of conductive polymer aqueous dispersion (1) and 216 g of conductive polymer aqueous dispersion (3).
[0084] (Examples 1 to 5) A conductive polymer dispersion having a polyanion-doped conductive polymer concentration of 12 mass% was obtained in the same manner as in Example 1-1, except that the conductive polymer aqueous dispersion was changed to a mixture of 60 g of conductive polymer aqueous dispersion (2) and 216 g of conductive polymer aqueous dispersion (3).
[0085] (Examples 1 to 6) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 79.9 g and the amount of dimethyl sulfoxide was 0.1 g.
[0086] (Examples 1 to 7) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 50 g and the amount of dimethyl sulfoxide was 30 g.
[0087] (Examples 1 to 8) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 40 g and the amount of dimethyl sulfoxide was 50 g.
[0088] (Examples 1 to 9) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 79 g and the amount of dimethyl sulfoxide was 1 g.
[0089] (Examples 1 to 10) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 90 g and the amount of dimethyl sulfoxide was 1 g.
[0090] (Examples 1 to 11) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 34 g and the amount of dimethyl sulfoxide was 10 g.
[0091] (Examples 1 to 12) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 44 g and the amount of dimethyl sulfoxide was 10 g.
[0092] (Examples 1 to 13) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 79 g and the amount of dimethyl sulfoxide was 10 g.
[0093] (Examples 1-14) A conductive polymer dispersion liquid in which the concentration of the conductive polymer doped with a polyanion was 6 mass % was obtained in the same manner as in Example 1-1, except that ethylene glycol was used instead of propylene glycol.
[0094] (Examples 1 to 15) A conductive polymer dispersion liquid in which the concentration of the conductive polymer doped with a polyanion was 6 mass % was obtained in the same manner as in Example 1-1, except that glycerin was used instead of propylene glycol.
[0095] (Examples 1 to 16) A conductive polymer dispersion liquid in which the concentration of the conductive polymer doped with a polyanion was 6 mass % was obtained in the same manner as in Example 1-1, except that N-methylformamide was used instead of dimethyl sulfoxide.
[0096] (Examples 1-17) A conductive polymer dispersion liquid in which the concentration of the conductive polymer doped with a polyanion was 6 mass % was obtained in the same manner as in Example 1-1, except that N,N-dimethylformamide was used instead of dimethyl sulfoxide.
[0097] (Comparative Example 1-1) A conductive polymer dispersion liquid in which the concentration of the conductive polymer doped with a polyanion was 6 mass % was obtained in the same manner as in Example 1-1, except that propylene glycol and dimethyl sulfoxide were not added.
[0098] (Comparative Example 1-2) A conductive polymer dispersion liquid having a polyanion-doped conductive polymer concentration of 6 mass % was obtained in the same manner as in Example 1-1, except that the amount of propylene glycol was 80 g and dimethyl sulfoxide was not added.
[0099] (Comparative Example 1-3) To 300 g of the conductive polymer aqueous dispersion (1), 60 g of propylene glycol and 20 g of acetonitrile (boiling point 82°C) were added as solvents, and the mixture was stirred with a stirrer for 1 hour, and water was removed under reduced pressure using an evaporator. At this time, acetonitrile was distilled together with water, so water was removed while adding 20 g of acetonitrile in five separate portions, thereby obtaining a conductive polymer dispersion with a concentration of 6% by mass of the conductive polymer doped with polyanion.
[0100] (Comparative Examples 1-4) The treatment was carried out in the same manner as in Example 1-1, except that isopropyl alcohol (IPA) was added instead of propylene glycol, but the conductive polymer aggregated during the removal of water under reduced pressure, and no dispersion was obtained. For this reason, the preparation of a conductive polymer film, which will be described later, was not carried out for this Comparative Example 1-4.
[0101] The compositions of the conductive polymer dispersions of the examples and comparative examples are shown in Table 1. The "conductive polymer" in Table 1 is doped with a polyanion. Furthermore, in the "state of dispersion" in Table 1, "dispersion" means that the conductive polymer is well dispersed in the liquid, and "aggregation" means that the conductive polymer is aggregated in the liquid.
[0102] [Table 1]
[0103] <Conductive polymer film> (Example 2-1) The conductive polymer dispersion of Example 1 was applied by screen printing (using a 400 mesh screen) onto a polyethylene terephthalate (PET) film ("Cosmoshine A-4360" (product name) manufactured by Toyobo Co., Ltd.), and dried at 150°C for 30 minutes to obtain a conductive polymer film.
[0104] The above printing was carried out 20 times in succession, and the number of sheets having faint marks or holes was visually checked for the 20 conductive polymer films obtained after drying.
[0105] In addition, for the conductive polymer films that had no smudges or holes, the surface resistance was measured at room temperature (25°C) using a Mitsubishi Chemical Analytech Loresta-GP (MCP-T610 type, in-line 4-point probe (ASP)), and the average value of all the measured film values was calculated.
[0106] (Examples 2-2 to 2-17 and Comparative Examples 2-1 to 2-3) Conductive polymer films were prepared in the same manner as in Example 2-1, except that the conductive polymer dispersion was changed to the conductive polymer dispersion of Examples 1-2 to 1-17 or Comparative Examples 1-1 to 1-3. The number of films out of 20 films that had fading or holes was counted, and for those that had no fading or holes, the surface resistance was measured in the same manner as in Example 2-1, and the average value of all the measured film values was calculated.
[0107] (Examples 2-18 and Comparative Examples 2-4) Conductive polymer films were produced in the same manner as in Example 2-1, except that the conductive polymer dispersion was changed to that of Example 1-1 or Comparative Example 1-1, and the substrate was changed to an aluminum etched foil. The number of films with fading or holes among the 20 films was counted, and the surface resistance of those without fading or holes was measured in the same manner as in Example 2-1, and the average value of all the measured film values was calculated.
[0108] (Examples 2-19 and Comparative Examples 2-5) Conductive polymer films were produced in the same manner as in Example 2-1, except that the conductive polymer dispersion was changed to that of Example 1-1 or Comparative Example 1-1, the substrate was changed to an aluminum etched foil, and the method of applying the conductive polymer dispersion to the substrate was changed to a method of immersing the substrate in the conductive polymer dispersion and then pulling it out. The number of films out of each of the 20 films that had fading or holes was counted, and those that had no fading or holes were measured for surface resistance in the same manner as in Example 2-1, and the average value of all the measured values of the films was calculated.
[0109] The evaluation results are shown in Table 2. The "surface resistance value" in Table 2 is the average value of all the measured film values, and "-" in the "surface resistance value" column means that the measurement was not possible.
[0110] [Table 2]
[0111] As shown in Table 2, the number of sheets on which fading or holes occurred was small for the conductive polymer films of Examples 2-1 to 2-17 formed using the conductive polymer dispersions of Examples 1-1 to 1-17 containing a compound having two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100° C. or higher. Furthermore, with the conductive polymer dispersions of Examples 1-1 to 1-17, no fading or holes occurred and it was possible to apply the conductive polymer dispersions by screen printing or immersion 14 or more times in succession.
[0112] In contrast, the conductive polymer dispersion of Comparative Example 1-1, which did not contain a compound containing two or more hydroxyl groups and an aprotic polar solvent with a boiling point of 100°C or higher, could not be screen printed on PET film, and smearing and holes were observed on aluminum etched foil after the third continuous printing and after the fifth continuous immersion. Moreover, the conductive polymer dispersions of Comparative Examples 1-2 and 1-3, which contained a compound containing two or more hydroxyl groups but did not contain an aprotic polar solvent with a boiling point of 100°C or higher, showed smearing after the seventh continuous printing and after the fourth continuous printing, respectively.
[0113] The conductive polymer films of Examples 2-1 to 2-19, which were formed using the conductive polymer dispersions of Examples 1-1 to 1-17 containing a compound having two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100° C. or higher, had lower average surface resistance values and better conductivity than the conductive polymer films of Comparative Examples 2-2 to 2-5, which were formed using the conductive polymer dispersions of Comparative Examples 1-1, which did not contain a compound having two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100° C. or higher, and Comparative Examples 1-2 and 1-3, which did not contain an aprotic polar solvent having a boiling point of 100° C. or higher. This is presumably because the conductive polymer films of Comparative Examples 2-2 to 2-5 had spots in the coating film (coating film of conductive polymer dispersion) formed by screen printing or immersion, even though no fading or holes were observed visually.
[0114] <Tantalum electrolytic capacitor> (Example 3-1) A chemical conversion treatment was performed by applying a voltage of 35 V to the tantalum sintered compact while it was immersed in a 0.1 mass% phosphoric acid aqueous solution, forming a dielectric layer made of a tantalum oxide film on the surface of the tantalum sintered compact, and producing a capacitor element with a set ESR of 20 mΩ or less, a set capacitance of 30 μF or more, a rated voltage of 12 V, and a set leakage current of 10 μA or less.
[0115] The capacitor element was immersed in an ethanol solution of 3,4-ethylenedioxythiophene with a concentration of 35% by mass, removed after 1 minute, and left for 5 minutes. Then, the capacitor element was immersed in an oxidizer / dopant solution consisting of a mixture of a 50% by mass phenolsulfonate butylamine aqueous solution (pH 5) and a 30% by mass ammonium persulfate aqueous solution in a mass ratio of 1:1, removed after 30 seconds, left at room temperature for 30 minutes, and then heated at 50°C for 10 minutes to polymerize. After polymerization, the capacitor element was immersed in water, left for 30 minutes, removed, and dried at 70°C for 30 minutes. This operation was repeated six times to form a solid electrolyte underlayer made of a conductive polymer on the capacitor element.
[0116] As described above, 20 capacitor elements on which a solid electrolyte underlayer made of a conductive polymer was formed by so-called "in situ polymerization" were immersed in the conductive polymer dispersion of Example 1-1 and then pulled out to coat the capacitor elements with the conductive polymer dispersion, and a solid electrolyte layer was formed by drying for 30 minutes at 150° C. The solid electrolyte layer after formation was visually checked for the presence or absence of fading and holes, and only for elements that did not have these, the solid electrolyte layer was covered with carbon paste and silver paste to produce a tantalum electrolytic capacitor.
[0117] (Comparative Example 3-1) A tantalum electrolytic capacitor was produced in the same manner as in Example 3-1, except that the conductive polymer dispersion was changed to the conductive polymer dispersion of Comparative Example 1-1.
[0118] The tantalum electrolytic capacitors of the examples and comparative examples were subjected to the following evaluations.
[0119] Equivalent series resistance (ESR): The ESR of each tantalum electrolytic capacitor was measured at 100 kHz under conditions of 25° C. using an LCR meter (4284A) manufactured by Hewlett Packard.
[0120] Capacitance (Cap): The Cap of each tantalum electrolytic capacitor was measured at 25° C. and 120 Hz using an LCR meter (4284A) manufactured by Hewlett Packard.
[0121] Leakage current (LC): A rated voltage of 25V was applied to each tantalum electrolytic capacitor for 60 seconds at 25℃, and then the LC was measured using a digital oscilloscope. If the measured LC value was 50μA or more, it could be determined that the LC defect occurred due to localized thin areas in the conductive polymer film caused by uneven coating of the conductive polymer dispersion.
[0122] The evaluation results are shown in Table 3.
[0123] [Table 3]
[0124] As shown in Table 3, the tantalum electrolytic capacitor of Example 3-1 having a solid electrolyte layer formed using the conductive polymer dispersion of Example 1-1 containing a compound having two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100°C or higher had excellent characteristics, such as no fading or holes in the solid electrolyte layer, a low ESR, a large Cap, and a suppressed LC.
[0125] On the other hand, in the case of the tantalum electrolytic capacitor of Comparative Example 3-1, which used the conductive polymer dispersion of Comparative Example 1-1 that did not contain a compound containing two or more hydroxyl groups and an aprotic polar solvent having a boiling point of 100°C or higher, a uniform coating could not be obtained, as in the case of coating on a PET film or an aluminum etched foil, and LC defects occurred that were thought to be caused by coating unevenness of the conductive polymer dispersion.
Claims
1. A conductive polymer dispersion liquid including a π-conjugated conductive polymer doped with a polyanion and a solvent, The solvent contains water, a compound containing two or more hydroxyl groups, and an aprotic polar solvent having a boiling point of 100° C. or higher, The water content is 5 to 40% by mass, the content of the compound containing two or more hydroxyl groups is 40 to 80 mass %, The content of the aprotic polar solvent having a boiling point of 100° C. or higher is 0.1 to 30% by mass, The conductive polymer dispersion liquid is characterized in that the polyanion is at least one of the following (A), (B) and (C): (A) Polystyrene sulfonic acid (B) A copolymer of styrenesulfonic acid and at least one non-sulfonic acid monomer selected from the group consisting of acrylic acid esters, methacrylic acid esters, and unsaturated hydrocarbon-containing alkoxysilane compounds or hydrolysates thereof. (C) Water-soluble polyester resin
2. 2. The conductive polymer dispersion according to claim 1, comprising at least one selected from the group consisting of dimethyl sulfoxide, N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N,N-dimethylacetamide as an aprotic polar solvent having a boiling point of 100° C. or higher.
3. 3. The conductive polymer dispersion according to claim 1, further comprising a polyhydric alcohol as the compound having two or more hydroxyl groups.
4. 4. The conductive polymer dispersion according to claim 3, further comprising, as the polyhydric alcohol, at least one selected from the group consisting of ethylene glycol, propylene glycol, butanediol and glycerin.
5. 5. A conductive polymer film formed by applying the conductive polymer dispersion according to claim 1 to a substrate and drying the resulting coating.
6. 6. An electrolytic capacitor comprising the conductive polymer film according to claim 5 as an electrolyte.
Citation Information
Patent Citations
Electronic devices containing acene-thiophene copolymers having silylethynyl groups
JP2009534853A
Solid electrolytic capacitor
JP2011060980A
Electroconductive polymer-containing coating material for forming a transparent electroconductive pattern, transparent electroconductive pattern-formed object, and method for manufacturing the same
JP2014152320A
Aqueous conductive polymer solution and conductive polymer film
JP2015157923A
Dispersion liquid of conductive polymer for production of electrolytic capacitor and electrolytic capacitor produced using the same
JP2016020414A